Primary leiomyosarcoma of kidney in a young adult (Indian Journal of Case Reports, 2018)
Primary renal leiomyosarcoma (LMS) is an extremely rare tumor constituting to <2% of all malignant renal tumors. Here, we present the case of a 28-year-old female with a right lower polar renal tumor, who underwent partial nephrectomy which on microscopy suggested LMS. Due to the lack of a follow-up protocol and low survival rates, regular imaging and a multidisciplinary approach were considered in the patient.